Les églises doubles de la Jordanie - Michel, Anne (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 1997)
Abstract The inventory of double churches from Jordan is limited : the episcopal group ofMadaba and the church of Amos and Casiseos (Khirbat al-Mukhayyat) must be discarded; the group of St. John the Baptist (Gerasa), the complex of St. Stephen (Umm al-Rasas) and probably the group excavated at Khirbat al-Samra should be added to the twin basilicas of the castrum Umm al-Rasas and to the episcopal group of Gerasa. The architectural organization of these groups and their functions display great diversity. Commemorations of martyrs and baptismal liturgies are important here as elsewhere.